Regeneration of partially decellularized tracheal scaffolds in a mouse model of orthotopic tracheal replacement. (June 2021) - Liu, Lumei; Dharmadhikari, Sayali; Shontz, Kimberly M; Tan, Zheng Hong; Spector, Barak M; Stephens, Brooke; Bergman, Maxwell; Manning, Amy; Zhao, Kai; Reynolds, Susan D; Breuer, Christopher K; Chiang, Tendy
Decellularized tracheal scaffolds offer a potential solution for the repair of long-segment tracheal defects. However, complete decellularization of trachea is complicated by tracheal collapse. We created a partially decellularized tracheal scaffold (DTS) and characterized regeneration in a mouse model of tracheal transplantation. All cell populations except chondrocytes were eliminated from DTS. DTS maintained graft integrity as well as its predominant extracellular matrix (ECM) proteins. We then assessed the performance of DTS in vivo. Grafts formed a functional epithelium by study endpoint (28 days). While initial chondrocyte viability was low, this was found to improve in vivo . We then used atomic force microscopy to quantify micromechanical properties of DTS, demonstrating that orthotopic implantation and graft regeneration lead to the restoration of native tracheal rigidity. We conclude that DTS preserves the cartilage ECM, supports neo-epithelialization, endothelialization and chondrocyte viability, and can serve as a potential solution for long-segment tracheal defects.